Case Report: Paroxysmal weakness of unilateral limb as an initial symptom in anti-LGI1 encephalitis: a report of five cases - Wang, Shan; Wang, Jirui; Li, Baizhu; Hu, Ning; Jin, Yingbin; Han, Shiyu; Shang, Xiuli (Frontiers in Immunology, 2023)
Anti-leucine-rich glioma-inactivated 1 (LGI1) encephalitis is the second most common kind of autoimmune encephalitis following anti-N-methyl-d-aspartate receptor (NMDAR) encephalitis. Anti-LGI1 encephalitis is characterized by cognitive impairment or rapid progressive dementia, psychiatric disorders, epileptic seizures, faciobrachial dystonic seizures (FBDS), and refractory hyponatremia. Recently, we found an atypical manifestation of anti-LGI1 encephalitis, in which paroxysmal limb weakness was the initial symptom. In this report, we describe five cases of anti-LGI1 encephalitis with paroxysmal limb weakness. Patients had similar presentations, where a sudden weakness involving a unilateral limb was observed, which lasted several seconds and occurred dozens of times each day, with the anti-LGI1 antibody being positive in both serum and cerebrospinal fluid (CSF). FBDS occurred after a mean of 12 days following paroxysmal limb weakness in three of five patients (Cases 1, 4, and 5). All patients were given high-dose steroid therapy, which had a good effect on their condition. Based on this report, we suggest that paroxysmal unilateral weakness may be a kind of epilepsy and be connected to FBDS. As an unusual neurological presentation, paroxysmal weakness can be included in the clinical manifestations of anti-LGI1 encephalitis, helping to raise awareness of the recognition of anti-LGI1 encephalitis in patients with this symptom and leading to early diagnosis and early treatment, which would contribute to improved clinical outcomes.